Covering the Face: The Complexities of Gendered Racialization in Europe - Moors, Annelies (Implicit religion, 2020)
The Dutch ban on face-veiling is a strong instantiation of the gendered racialization of Muslims in Europe. Racialization as a relation of power, with some in the position to categorize and impose an identity on others, produces and naturalizes difference. To justify the ban, politicians signified face-veiling as gendered oppression, as a security threat and as an obstacle to integration, bringing together ethical positions with affective and aesthetic sensibilities. The largely unheard narratives of face-veiling women, in contrast, highlighted the positive religious value of face-veiling and point to the state’s infringement on their freedom of religion, expression, and movement. As face-veiling women are simultaneously defined as victims to be saved and as threat to be removed from the public, their racialization is ambivalent. It is also multilayered, with debates on faceveiling not only producing a divide between Muslims and non-Muslims, but with some Muslims also involved in the racialization of other Muslims.